ผลกระทบจากวิกฤตเศรษฐกิจของประเทศญี่ปุ่นและเอเชียที่มีต่อการเคลื่อนย้ายการลงทุนทางตรงจากประเทศญี่ปุ่นสู่ประเทศในอาเซียน 4 และ 3 ประเทศอุตสาหกรรมใหม่ - พีรเดช ชูเกียรติขจร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research aims to study the influence that Japanese foreign direct investment had during the Japanese Financial Crisis in 1990 and the Asian Financial Crisis in 1997 by observing macroeconomic variables. The study evaluated from quantitative and descriptive study. This study employs the panel data, which is the dataset of ASEAN4 (Thailand, Indonesia, Malaysia and Philippine) during 1980 – 2010 and NIEs3 (Singapore, Hong Kong and South Korea) during 1970 – 2010. Panel cointegration and panel equation testing are applied to this study. According to Westerlund test, the result of Panel cointegration test in ASEAN4 shows that the exchange rate of host country (EXC) and the inflation rate of host country (INF) are significantly related with Japanese foreign direct investment in long term. Moreover, group testing shows that at least a country in ASEAN4 has the variables on government expenditure and the number of population are significantly related with Japanese foreign direct investment. The result of panel cointegration in NIEs3 shows that the exchange rate of host country (EXC), the inflation rate of host country (INF), the government expenditure (GOVEXP), the number of population of host country (POP) and exchange rate parabola (EXCSC) are significantly related with Japanese foreign direct investment in the long term. For the result of panel equation testing, the random effect is efficient and appropriate to estimate both the models of ASEAN4 and NIEs3.